Modelling of fracture processes in laminate composite plates with embedded delamination - Mikhail A. Tashkinov (Fracture and Structural Integrity)
This work is devoted to research and development of models for the processes of nucleation and growth of delamination in laminated composite materials. Possibilities of fracture mechanics approaches using virtual crack closure technique as well as progressive failure analysis based on the failure criteria are demonstrated. Influence of the initial delamination size on the rate of growth of the defect is studied. A comparative analysis of the applicability of fracture criteria to modeling of samples with delamination were performed, including implementation of element deletion algorithm. The numerical results obtained with the studied methods were compared.